Poky plastic perks up [polymer semiconductor]. - Moore, S.K (IEEE spectrum)
Material scientists in Britain and California have invented the first polymer semiconductor to perform almost as well as the type of silicon used to drive flat-panel displays. The new polymer was found to beat previous polymers by a factor of about six in terms of charge carrier mobility. Key to the team's success is the fact that its polymer is also a liquid crystal, which means charge can travel more quickly. Although the liquid crystal approach has certainly improved polymer's prospects, many research groups are hard at work improving the printability of small molecules.